DEVELOPMENT OF MODELS TO AID DECISION-MAKING IN THE MANAGEMENT OF Araucaria angustifolia (Bertol.) Kuntze - Souza, Isadora de Arruda; Hess, Andre Felipe; Costa, Emanuel Arnoni; da Silveira, Ana Claudia; Baldissera Schorr, Luiz Paulo; Atanazio, Kemely Alves (Floresta, 2020)
Operational research (OR) is a powerful tool for decision-making in optimizing forestry production planning. Thus, the objective of this study is to use the OR to solve forest regulation problems in a natural forest of Araucaria angustifolia (Bertol) Kuntze. The proposal for better management regime for the forest consisted in the elaboration of two OR problems using integer linear programming (ILP). I – the first aiming to maximize income for each regime; and the II – second aiming to define the best management alternative for three values of the De Liocourt q quotient of 1.1; 1.3 and 1.5, residual basal areas of 10.0, 12.0 and 14.0 m2.ha-1 and cutting cycles of 20, 25 and 30 years, creating thus 27 management scenarios. Despite the application of cutting cycles of 20, 25 and 30 years, the management alternative that best uses the resources and maximizes the income for this area of 84 ha, in the municipality of Lages, SC, is “q” = 1.3 with residual basal area of 12 m2.ha-1 for all cutting cycles. The removal of these trees in the forest will contribute to the maintenance of a future diametric structure, natural regeneration, species conservation and tree increment rate, as well as the maintenance of resources of the forest ecosystem.